The body and religion - Krajewska, Malwina (Body and society. Sociology of the body in research and theoretical concepts, 2023)
This chapter is devoted to the relations and dependencies occurring between the human body and various forms of religious life. The discussion considers their normative, theoretical and practical aspects. First, the investigated issues refer to the historical perspective, the starting point of which encompasses contradictory—medieval and renaissance—ways of viewing corporeality in Christian Europe. The narrations that follow are concerned with the ways in which the human body is viewed throughout world religions: Islam, in which the approach propagating care and attention to the body is common; Hinduism, in which the body is a home for the soul, only a temporary manifestation entangled in the cycle of rebirth; Buddhism, for which the body is a tool to overcome suffering and to achieve the state of unconditioned happiness – enlightenment. The chapter is also devoted to the methods and techniques of using the body, which are practised by various world religions. Bodily regimens are discussed, which are supposed to control human urges, facilitate maintaining social order and raise productivity. Apart from the interpretations of human corporeality and the methods of using it, the chapter devotes significant attention to its role in ceremonies and rituals. A crucial multi-faceted symbolic dimension referring to the bodies of the seculars and saints as well as the deceased and the relics is also discussed. In addition to numerous examples of interpreting, shaping and engaging in religious practices, a reader will also find here many examples of theoretical narrations authored by classical and contemporary sociologists and anthropologists.